Dissociative Social Interaction Patterns of Clove Farmers in Anrang Village - Abdur Rahman Syam; Firdaus W. Suhaeb; Ashari Ismail (Asha Publishing, 2026)
The purpose of this research is to examine: (1) The potential for dissociative interactions between clove farmers in Anrang Village; and (2) the forms of efforts made to overcome dissociative interactions between clove farmers. This research applies a qualitative method using a descriptive approach. The researcher chose a qualitative approach to achieve the research objectives through data collection using observation, interview and documentation techniques. The instruments used include observation guidelines, interview guidelines, and documentation. Interviewing 22 informants, namely clove farmers in Anrang Village. In the data analysis process, there are four stages, namely data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that: (1) The potential for dissociative social interactions between farmers in Anrang Village is divided into three, namely a) Social jealousy due to differences in clove harvests with those of others and jealousy over land distribution and land inheritance; b) Competition marked by the closure of road and irrigation access, unhealthy economic competition among farmers, theft of clove seeds and plants, price competition between traders, competition to control more fertile and productive land; c) Provocation marked by the emergence of a third party in the dispute between the two parties leading to physical violence to murder, provocation from outside parties or families that worsens land disputes, social incitement, and provocation that ends in the destruction of other people's clove fields. As for (2) the resolution of dissociative interactions that occur between clove farmers in Anrang Village is divided into 2 efforts, namely: a) Negotiation with dialogue between the two parties directly involved and a family approach; b) Mediation involving the hamlet head, village head, or community leaders as a third party in resolving dissociative interactions between clove farmers by providing solutions to both parties in conflict so as to obtain an agreeable result. Most of the conflicts that occur between clove farmers are resolved through mediation.